2016
DOI: 10.1186/s12929-016-0244-5
|View full text |Cite
|
Sign up to set email alerts
|

Identifying N-linked glycan moiety and motifs in the cysteine-rich domain critical for N-glycosylation and intracellular trafficking of SR-AI and MARCO

Abstract: BackgroundThe accumulation of soluble oligomeric amyloid-β peptide (oAβ) proceeding the formation of senile plaques contributes to synaptic and memory deficits in Alzheimer’s disease. Our previous studies have indentified scavenger receptor A (SR-A), especially SR-A type I (SR-AI), as prominent scavenger receptors on mediating oAβ clearance by microglia while glycan moiety and scavenger receptor cysteine-rich (SRCR) domain may play the critical role. Macrophage receptor with collagenous structure (MARCO), anot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…Glycans attached to proteins are closely related to protein stability, trafficking, signaling, and cell–cell interaction . N-linked glycosylation of proteins, one of the most prevalent post-translational modifications in eukaryotes, significantly affects protein folding, stability, and function. , However, the heterogeneity of N-glycan in natural and recombinant glycoproteins greatly hampered the investigation of the roles of glycan in various biological processes.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Glycans attached to proteins are closely related to protein stability, trafficking, signaling, and cell–cell interaction . N-linked glycosylation of proteins, one of the most prevalent post-translational modifications in eukaryotes, significantly affects protein folding, stability, and function. , However, the heterogeneity of N-glycan in natural and recombinant glycoproteins greatly hampered the investigation of the roles of glycan in various biological processes.…”
mentioning
confidence: 99%
“…G lycans attached to proteins are closely related to protein stability, 1 trafficking, 2 signaling, 3 and cell−cell interaction. 4 N-linked glycosylation of proteins, one of the most prevalent post-translational modifications in eukaryotes, significantly affects protein folding, stability, and function.…”
mentioning
confidence: 99%
“…To determine the binding region of MARCO-TST necessary for its association with PLOD2, we obtained a series of MARCO-TST truncation mutants ( SI Appendix , Fig. S6 E , Upper Panel ) according to the domains of MARCO ( 30 ). We found that the transmembrane domain of MARCO-TST was the major region binding to PLOD2 ( SI Appendix , Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Based on their protein sequence, SRs are classified into 10 families (A-J). It has been shown that scavenger receptor class A (SR-A) and class B type 1 (SR-B1), as well as CD36 participate in Aβ clearance [252254]. SR-A which is expressed on microglial cells and macrophages is implicated in Aβ phagocytosis [255].…”
Section: Receptor-mediated Aβ Phagocytosismentioning
confidence: 99%